Ion clustering in aqueous salt solutions near the liquid/vapor interface - Smith, J.D.; Rick, S.W. (Condensed Matter Physics, 2016)
Molecular dynamics simulations of aqueous NaCl, KCl, NaI, and KI solutions are used to study the effects of salts on the properties of the liquid/vapor interface. The simulations use the models which include both charge transfer and polarization effects. Pairing and the formation of larger ion clusters occurs both in the bulk and surface region, with a decreased tendency to form larger clusters near the interface. An analysis of the roughness of the surface reveals that the chloride salts, which have less tendency to be near the surface, have a roughness that is less than pure water, while the iodide salts, which have a greater surface affinity, have a larger roughness. This suggests that ions away from the surface and ions near the surface affect the interface in opposite ways. Моделювання методом молекулярної динамiки водних розчинiв NaCl, KCl, NaI, i KI використовується для
дослiдження ефектiв солi на властивостi границi роздiлу рiдина/пара. Симуляцiї використовують моделi,
якi включають i зарядовий перенос, i поляризацiйнi ефекти. Парування i формування бiльших iонних
кластерiв має мiсце i в об’ємi, i в поверхневiй областi з тенденцiєю до зменшення формування великих
кластерiв бiля границi роздiлу. Аналiз нерiвностi поверхнi вказує, що хлориднi солi, якi мають меншу
тенденцiю бути бiля поверхнi, мають нерiвнiсть, що є меншою, нiж у чистiй водi, тодi як йодовi солi,
якi мають бiльшу поверхневу спорiдненiсть, мають бiльшу нерiвнiсть. Це передбачає, що iони здаля вiд
поверхнi та iони поблизу поверхнi впливають на границю роздiлу протилежним чином.